A novel analytical method for the analysis of a bi-concave cable-truss footbridge. (15th September 2016) - Sadaoui, Arezki; Lattari, Kamel; Khennane, Amar
Highlights: Development of closed form solutions for cable truss. The solution covers wide spectra of loads. The stays are included in the calculations. Abstract: Bi-concave cable truss systems are not only aesthetically appealing but they also offer elegant solutions for spanning large spans required in modern buildings such as convention centres, sport arenas and bridges. These structures, however, are notoriously difficult to model correctly using non-numerical based methods. The existing analytical methods are limited to uniformly distributed loads on half or the entire span, and do not include the stays in the calculations. This paper details a novel analytical method that not only covers wide spectra of loads, including both uniformly distributed and concentrated loads on any part of the span, but also includes the stays in the calculations. The mathematical formulation was based on the fundamental assumption that the hangers form a continuous and inextensible diaphragm. The main two nonlinear equations describing the cable thrusts, unknowns of the problem, were calculated using an orthogonal displacement equation based on the boundary conditions of the cable ends at the anchorages. The predicted results are compared to finite element analysis, and good agreement was found across all the load configurations. The presented method was found to be very efficient and reliable.